Tingkat keberhasilan inseminasi buatan (IB) pada peternakan sapi potong di Kelurahan Kalampangan Kecamatan Sabangau Kota Palangka Raya - K Kastalani; H Herlinae; Ady Kurniawan (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
The study aims to determine the success rate of Artificial Insemination in beef cattle farm in the Kalampangan village, district of Sebanga, Palangka Raya City. The research method used is descriptive method, the implementation of reseach by direct survey method of breeders whose livestock habe been artificially inseminated in the period of January to December 2016. The variables observed in this study were breeders and inseminators. The succsess rate of artificial insemination in beef cattle farm in the Kalampangan Village, district of Sabangau, Palangka Raya City viewed from service per conception (S/C) of 1,66 ± 0,30, Conception Rate (CR) of 62 %, and Non Return Rate (NRR) of 65 %. Besides the succsess rate of artificial insemination was also determined by the knowledge of breeders and inseminator officers. Keywords : Artificial Insemination, Service per Conception, Conception Rate, Non Return Rate.